PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ROKOK DJARUM SUPER DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI - Erni Widajanti, Dedy Kurniawan & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this research was: 1) to analyze the significance of the influence of promotion, price and customer satisfaction towards purchasing decision Smoking Djarum Super on society in the village Central sub-district of Sragen. 2) to analyze the effect of moderation in consumer satisfaction influence promotion and price of purchase Smoking Djarum Super on society in the village Central sub-district of Sragen. Research methods using method survey. The population in this research community teenagers and adults who smoke Djarum Super sex with males in the Village Central sub-district of Sragen. In research technique sampling using a purposive sampling, the number of samples that used as many as 100 people. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test, the coefficient of determination and analysis of the absolute difference. The research results obtained conclusions: there is a significant influence on promotion, price and customer satisfaction towards purchasing decision Smoking Djarum Super on society in the village Central sub-district of Sragen. Consumer satisfaction does not moderate the influence of promotions and price of purchase Smoking Djarum Super on society in the village Central sub-district of Sragen. \ Keywords: promotion, price, consumer satisfaction and purchasing decisions.